Model Dakwah Purifikasi: Strategi Penguatan Tauhid oleh Majelis Tafsir Al-Qur’an di Kabupaten Langkat - Ahmad Ali Nafiah (Young Journal of Social Sciences and Humanities, 2026)
The Majelis Tafsir Al-Qur’an (MTA) in Hinai District, Langkat Regency, holds a strategic potential as an agent of religious transformation through da’wah (Islamic outreach), focusing on the teachings of aqidah (creed) and a direct understanding of the Qur’an and authentic Hadith. However, this role is confronted by complex challenges, including the diversity of religious interpretations within the community, the deep-rooted local traditions, and the influence of globalization and cultural acculturation, which potentially undermine the foundations of tawhid (monotheism). The primary objective of this research is to examine the role of MTA in strengthening the community's aqidah, as well as identifying the effective da’wah programs and methods within the socio-cultural context of Hinai District. This study employed a qualitative method with a case study approach, utilizing in-depth interviews, observations, and documentation involving MTA administrators and congregants. The findings indicate that MTA plays a significant role in reinforcing the understanding of tawhid through a systematic and adaptive scripturalist approach, such as sequential tafsir (exegesis) studies, Q&A sessions, group discussions, and socio-religious activities. These approaches have encouraged a shift in religious patterns from traditional taqlid (unquestioning imitation) toward critical and rational ittiba’ (following with evidence). This research concludes that MTA serves as a relevant and sustainable model of purification da’wah in fostering the purity of aqidah and the quality of faith amidst contemporary socio-cultural challenges.